Strategi Komunikasi Dinas Perhubungan Kabupaten Buton Utara Dalam Mensosialisasikan Keselamatan Berlalu Lintas - Suandi, Fikry; Alamsyah, Alamsyah; Sukma, Agus Hitopa Sukma; Pranawukir, Iswahyu (Prisani Cendekia Institute, 2025)
This study aims to determine the communication strategies implemented by the North Buton Regency Transportation Agency in its Traffic Safety Socialization activities and to identify the factors that hinder its implementation. This study uses qualitative research methods that produce descriptive data in the form of written or spoken words from people and observed behavior. Data were obtained using interview, observation, documentation, and triangulation methods from the source of the results of the Communication Strategy research conducted by the Safety Guidance Team (Bimkos Team) of the North Buton Regency Transportation Agency in the socialization program by identifying the communication targets, reviewing the message objectives through the material delivered and traffic order videos displayed in the socialization activities. Using face-to-face communication media (direct) with presentations and various official online media of the North Regency pioneer student community. Traffic Safety Guidance (Bimkes Team) as a communicator in communication plays a role in persuading its audience with an active speaking method in socialization activities. As well as the attractiveness and credibility of sources in the traffic safety socialization program. The communication strategy implemented by the Bimkos Team is intended to minimize the high level of accidents that occur. The results of the study show an increase in awareness and concern among students to comply with traffic regulations for the sake of mutual safety, but there are still obstacles that prevent this socicoalization program from running optimally. The obstacles experienced by the North Buton Regency Transportation Agency in implementing the Traffic Safety Socialization program come from internal and external factors